Peran Foreign Direct Investment dalam Pembangunan Industri Nasional : Studi Kasus Hyundai Motor Company - Diva Sabrina (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Foreign direct investment (FDI) is one of the driving forces of economic development in developing countries, including Indonesia. This article analyzes the factors that drive Hyundai Motor Company to invest in Indonesia and the impacts of the investment on national and regional economic growth. This study uses a normative and descriptive-analytical juridical approach by examining laws and regulations, government policies, and relevant international investment theories. The results of the analysis show that Hyundai's decision to invest in Indonesia is influenced by various strategic factors such as the potential of the domestic automotive market, the availability of nickel resources, government policy support, competitive labor costs, and the convenience provided in the framework of the IK-CEPA bilateral agreement. This investment has a positive impact in the form of job creation, technology transfer, increasing the capacity of the national electric vehicle industry, and contributing to regional economic development. This study also highlights the importance of policy continuity and legal protection for investors in strengthening the clean energy-based industrial ecosystem in Indonesia.